Pelatihan Olah Vokal dan Seni Musik di SD Negeri 01 Ungaran - Suhirno, Suhirno; Hesti Yunitiara Rizqi (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Vocal and musical arts training at SD Negeri 01 Ungaran aims to improve students' musical abilities and develop artistic talents among teenagers. This program involves a series of activities such as vocal training, introduction to various musical instruments, and musical techniques. Through this training, students are expected to be able to understand the basics of good vocal technique, become familiar with various musical genres, and be able to perform confidently in various school events and competitions. Apart from that, this activity also aims to strengthen social relations between students through cooperation and collaboration in music groups. The results of this program show significant improvements in students' musical abilities as well as a greater appreciation for the art of music. With this training, it is hoped that it can cultivate a talented young generation and contribute to the world of musical arts in the future.